BUILDING A KNOWLEDGE-BASED ECONOMY IN INDONESIA: TRIPARTITE COORDINATION BETWEEN HUMAN RESOURCE DEVELOPMENT, RESEARCH, AND INDUSTRY - Dewi, Anggia Utami (Universitas Padjadjaran, 2024)
Indonesia aims to be a developed economy based on knowledge in 2045, hence the coordination between the training of human resources as knowledge transfer, knowledge production, and industrial development becomes crucial. This research analyzes the tripartite coordination between human resource development, research, and industry under the context of knowledge-based economic development in Indonesia. Through a qualitative desk study, this research attempts to inquire about the national-level reform policies and strategies to enhance coordination and see the main actor behind and within the initiative processes. The key findings highlight that the national-level reform initiatives to enhance the trilateral sectors coordination can be seen in four dimensions, which are legal frameworks; policy schemes; consolidating structures; and funding schemes, with the focus on the improvement of quality, relevance, and competitiveness of higher education in supporting the quest to build knowledge economy. Further, the results have also shown that the government is still the dominant actor behind the principal changes, and there has been a changing pattern of reform policies in favor of industrial linkage, particularly since the second term of Joko Widodo's administration. From the evidence found in this study, it can be concluded that Indonesia as a developing economic and higher education system follows the global convergence in building a knowledge-driven economy through government-led coordination among the training of human resources, research, and industry. However, the distinctive context from the Indonesian experience also provides the divergence of the global trend. Hence, this research has contributed to the discourse of higher education in the knowledge economy particularly from developing systems in Southeast Asia. Indonesia bertujuan untuk menjadi negara ekonomi maju berbasis pengetahuan di tahun 2045, karenanya koordinasi antara pelatihan sumber daya manusia sebagai transfer pengetahuan, produksi pengetahuan, dan pembangunan industrial menjadi sangat penting. Penelitian ini menganalisis koordinasi tripartit antara pengembangan sumber daya manusia, penelitian, dan industri dalam konteks pembangunan ekonomi berbasis pengetahuan di Indonesia. Melalui desk study kualitatif, penelitian ini berupaya untuk mengetahui kebijakan dan strategi reformasi di tingkat nasional untuk meningkatkan koordinasi dan melihat aktor utama di balik dan di dalam proses inisiatif tersebut. Temuan-temuan utama menyoroti bahwa inisiatif reformasi tingkat nasional untuk meningkatkan koordinasi sektor trilateral dapat dilihat dalam empat dimensi, yaitu kerangka hukum; skema kebijakan; struktur konsolidasi; dan skema pendanaan, dengan fokus pada peningkatan kualitas, relevansi, dan daya saing pendidikan tinggi dalam mendukung upaya membangun ekonomi pengetahuan. Lebih lanjut, hasil penelitian juga menunjukkan bahwa pemerintah masih menjadi aktor dominan di balik perubahan-perubahan mendasar tersebut, dan terdapat perubahan pola kebijakan reformasi yang mendukung hubungan industrial, terutama sejak masa jabatan kedua pemerintahan Joko Widodo. Dari bukti-bukti yang ditemukan dalam penelitian ini, dapat disimpulkan bahwa Indonesia sebagai negara berkembang dengan sistem ekonomi dan pendidikan tinggi mengikuti konvergensi global dalam membangun ekonomi berbasis pengetahuan melalui koordinasi yang dipimpin pemerintah antara pelatihan sumber daya manusia, penelitian, dan industri. Namun, konteks berbeda dari pengalaman Indonesia juga memberikan perbedaan dalam tren global. Oleh karena itu, penelitian ini telah berkontribusi pada wacana pendidikan tinggi dalam ekonomi pengetahuan khususnya dari sistem yang sedang berkembang di Asia Tenggara.